Determination of specific and non-specific parameters of saluang belum (Luvunga sarmentosa (Blume) Kurz.) root extract and quantification of its total flavonoid content - Dina Fadhila Zahra; M. Ikhwan Rizki; Wathan, Nashrul (Jurnal Ilmiah Farmasi, 2025)
Background: Saluang belum (Luvunga sarmentosa (Blume) Kurz.) is an endemic plant native to the Kalimantan region. The Dayak people traditionally consume a decoction of L. sarmentosa root to improve stamina. Previous research has confirmed that the roots of L. sarmentosa possess antioxidant properties.Objective: This study aims to determine the characterization values of both specific and nonspecific parameters of the ethanol extract from L. sarmentosa roots, as well as to assess the total flavonoid content.Method: The research samples were collected from Timpah Village, Central Kalimantan. The methods for standardization employed the general standard parameters for Indonesian Herbal Extracts and the Pharmacopoeia. Specific parameters include the characteristics of the extract, phytochemical screening, and thin-layer chromatography profiles, while nonspecific parameters consist of determining water content, total ash, acid-insoluble ash content, and heavy metal contaminants (Pb, Cd, and Hg). The total flavonoid content was determined using a colorimetric method with AlCl₃ and quercetin as the standard.Results: The extract was characterized as a thick, yellowish-brown substance with a strong, distinct odor and a bitter taste. It contains alkaloids, flavonoids, tannins, terpenoids, and steroids. The TLC profile revealed four distinct spots using a non-polar eluent and six spots with a polar eluent. The extract yield was 8.57%, with an average water content of 2.43±0.15%, total ash content of 1.50%, and acid-insoluble ash content of 1.00±0.87%. Heavy metal contamination levels were determined as follows: Pb < 0.001 mg/kg, Cd 0.446 mg/kg, and Hg 2.077 mg/kg. The total flavonoid content of the extract was quantified at 6.9147 ± 0.0083 mg QE/g.Conclusion: All specific and non-specific parameters of the extract meet the requirements except for the heavy metal contaminants of Hg and Cd, which are still within the threshold limits set by BPOM. Meanwhile, the total flavonoid content measured was 6.9147 ± 0.0083 mg QE/g.